Impact of BMI on basal LH in premenarcheal girls with idiopathic central precocious puberty - Yuan, Xin; Zhang, Ying; Zhang, Jing; Wu, Wenyong; Chen, Ruimin (Frontiers in Endocrinology, 2026)
AimTo examined whether body mass index (BMI) affects basal gonadotropin secretion in premenarcheal girls with idiopathic central precocious puberty (ICPP).MethodsThis retrospective single-center study involved girls diagnosed with ICPP. They were classified into underweight, normal weight, overweight, and obesity groups based on BMI-z scores. Clinical assessments included measurements of uterine and ovarian volumes and bone age (BA). Basal and gonadotropin-releasing hormone-stimulated luteinizing hormone (LH) and follicle-stimulating hormone (FSH) levels were measured. Correlation and partial correlation analyses were performed to explore relationships between BMI and aforesaid clinical assessments.Results1077 girls (7.58 ± 0.91 years old) with ICPP were subdivided as normal weight (n=613), underweight (n=102), overweight(n=235), and obesity(n=115). Significant differences in clinical and hormonal characteristics were observed across weight groups. Underweight girls had lower basal LH as well as basal LH/FSH ratios compared to overweight and obesity groups. Overweight girls had higher basal LH than normal weight girls. Girls with obesity had no significant difference in basal LH compared to normal weight girls but had a positive within-group correlation between BMI and basal LH. Overall, BMI was positively correlated with basal LH, basal FSH, basal LH/FSH ratio, BA, BA-CA, uterine size and ovarian size, all of which persisted after adjusting for age and disease course.ConclusionBMI is associated with basal LH in girls with ICPP, with distinct patterns across different weight groups. These findings highlight the importance of considering BMI when interpreting basal LH levels in the diagnosis of ICPP.